Revisiting education and training programs: Geoarchaeology as a driver of interdisciplinary reasoning - Oosterbeek, Luiz; Adewumi, Opeyemi L.; Rosina, Pierluigi; Gomes, Hugo; Cura, Pedro; Garcês, Sara (Frontiers in Earth Science, 2022)
A core problem of contemporary society is rooted in the educational system and the divides created between the humanities and sciences that have prevented integrated reasoning. This problem affects society at large and has severely impacted the mindset of leadership, precluding in-depth debates involving citizens that lack an understanding of the basic notions and concepts that drive other agencies. Thus, the Lisbon Declaration, approved at the European Humanities Conference based on proposals by UNESCO, CIPSH, and FCT, calls for the integrated teaching of humanities and sciences units at all levels of education, including the doctoral level. This chapter discusses the potential contribution of geoarchaeology towards that aim, as this discipline sits at the heart of the humanities-sciences interaction, thus bridging science methods with human behavior. Geoarchaeology is one of the most important archaeological research methods that offers unprecedented levels of integration between disciplines and geoarchaeological research. It is a good example of how geosciences can contribute towards re-thinking education, in terms of research-based education: learning to research, learning that research on the earth and humans is by nature interdisciplinary, learning to design answerable questions, learning to frame scientific analysis within wider meanings and prospects, and fostering an understanding of the truth and the criteria for truth. This topic is a unique bridge between both human and earth sciences and between science and human behavior, which play pivotal roles in communicating and educating about sustainability. The multidisciplinary dimensions of geoarchaeological approaches have encouraged continuous development and innovation of methods and approaches that have provided new possibilities for explorations in geosciences, research on earth and humans, learning to design answerable questions, and fostering an understanding of truth and the criteria for truth. This text discusses two examples: pigment analysis and micromorphology. Pigment analysis relates scientific methods with rock and mobile art, and also involves experimentation in the making of the art itself, which is a powerful didactic tool, thus linking science with daily observed realities and related cultural traits. Micromorphology is a geoarchaeological methodology currently applied to research, which provides a unique insight into the interdisciplinarity and multidisciplinary relationships associated with humans and society. Despite the complexity of this approach, it provides easily understood information on various segments of society; e.g., soil formation, thus making it one of the most effective tools in the Earth Sciences sector contributing to sustainability and related to daily behavior practices.